Psychological well-being: theoretical approaches to the concept definition - Mozharovska , Tetiana (Psychological Prospects Journal, 2021)
Purpose. In recent decades, the number of studies of happiness has increased rapidly, which led to the emergence of new empirical knowledge about the mechanisms, ways, peculiarities, and processes that contribute to a personality’s happiness and well-being. In today’s world pandemic terms caused by coronavirus SARS-COV-2, most people found themselves in unusual conditions, which influenced the change of style and lifeway of everyone. People had to look for new ways to ensure and implement their wellfare and the well-being of others. The purpose of the article lies in the theoretical analysis of the study of the problem of psychological well-being of a personality. Methods. The theoretical methods are used, in particular, analysis, synthesis, generalization, systematization, and theoretical modelling to clarify the essence of the basic concepts of the researched phenomenon. Results. The analysis of approaches to the determination of well-being and its types is carried out as the result of theoretical surveys on this issue. The tendency to combine different theories and approaches to the analysis of psychological and subjective well-being into the single complex study of wellbeing is revealed. The components of psychological wellbeing are described. Conclusions. The conclusions of scientific investigations of the researched phenomenon include the description and grounding of the dimensions of psychological well-being, namely: personality, social, material, physical and spiritual. The personality dimension of psychological well-being considers the subjective indicator of the inner feeling of happiness and comfort. The social context of psychological well-being is conditioned by the degree of personality’s satisfaction with the quality of own interpersonal relationships, social roles and social status. The material dimension of psychological well-being is predetermined by the subjective assessment of the real wealth of a personality and the objective comparison of the latter with the desired one. It is defined by the ability to meet the vital needs of a personality and contribute to spiritual development. The physical dimension of psychological well-being is determined by the level of human health and implies the presence of potential (reserve) abilities of organism, adaptation adequacy to the environmental changes, tolerance to unpredictable and stressful events. The spiritual dimension of psychological well-being is determined by a personality’s affiliation to the culture and community with which this personality is identified; involves a critical attitude towards oneself and own activities.